RELATIONSHIP BETWEEN TEACHERS SELF EFFICACY AND ACADEMIC PERFORMANCE OF SENIOR SECONDARY SCHOOL STUDENTS IN COMPUTER STUDIES IN BORNO STATE, NIGERIA - Garba Charles Dibal; Danjuma, I. M.; Musa O. D. (Galaxy International Interdisciplinary Research Journal, 2022)
This study investigated the Relationship Between Teachers’ Self-Efficacy and Academic Performance of Senior Secondary School Students in Computer Studies in Borno State, Nigeria. The research design adopted for the study is correlational research design. The population of the study comprised of 28,891 senior secondary school II students and all 156 computer studies teachers from 83 public schools in the study area. Multistage cluster sampling was used to select sample for the study. Sample size of three hundred and ninety-six (396) SS II students were selected from population using Yamane method of (1967) and 40 SS II computer studies teachers were purposively sampled from the sample schools. Two research instruments were used for data collection in the study namely, Teacher Self-Efficacy (that has three components) and Computer Studies Achievement Test. The reliability index for the two research instruments were 0.93 and 0.738 respectively. Data collected were analyzed using Pearson’s Product Moment Correlation. one research question and one research hypothesis were investigated using Pearson’s Product Moment Correlation. Research hypothesis were tested at 0.05 level of significance. The results of study revealed that there exists positive significant relationship between Computer Studies teachers’ self-efficacy and students’ academic performance in Borno State Nigeria. Hence, it was recommended that teachers should be more committed and optimistic to the profession in order to improve their self-efficacy so that they can prepare their students with what is expected of them.